“It’s something that I do every day.” Exploring interdisciplinarity and stakeholder engagement in tsunami science - Rödder, Simone; Schaumann, Felix (Frontiers in Earth Science, 2022)
Tsunamis are natural hazards that can have devastating societal impacts. While tsunamis cannot be prevented, their risk to coastal communities can be mitigated through targeted measures such as early warning, evacuation training or tsunami-aware spatial planning. The particularities of tsunamis – being rare events with high impact and a short yet operable time span for warning – structure the associated research approaches and sociotechnical innovations. In this paper, we explore interdisciplinary knowledge integration and stakeholder engagement in tsunami science based on interviews with researchers from various tsunami-related fields. We find that the interviewees’ academic identities are typically grounded in a disciplinary core, out of which they subsequently cross boundaries. For all respondents, however, it is a matter of course that becoming and being a member of the tsunami community includes the need to communicate across boundaries. Our results show that the idea of early warning unites the tsunami field. Notably, however, it is not the material technology but the political goal of effective early warning that holds an integrative function across disciplines. Furthermore, we find modelling to be seen as the “backbone of everything” tsunami- related, which in combination with visualisation techniques such as a global map of tsunami risks also serves to integrate stakeholders beyond the tsunami research community. Interviewees mention the interaction between scientists and engineers as the exemplary interdisciplinary collaboration in tsunami science. There were fewer examples of collaborations with social scientists, rendering this a demand rather than a lived reality in current tsunami science. Despite the widely shared view that stakeholder engagement is an important element of tsunami science, respondents emphasise the associated challenges and indicate that this practice is not yet sufficiently institutionalised.